2023
DOI: 10.1037/mac0000105
|View full text |Cite
|
Sign up to set email alerts
|

Scripts, agents, and interpretations: Delving into the valence biases of mental time travel.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For instance, Zerr et al (2023) suggest that the valence-based dissociation between personal and collective cognition may be tied to the fluency-based cueing techniques that have dominated early studies in this area. Moreover, Zerr et al (2023) and Habermas et al (2023) suggest that additional work with narrative-based techniques is needed to better understand not just what events come to mind but the situational context, meaning, and function of those events (see also Daley et al, 2023; Hirst & Topçu, 2023).…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Zerr et al (2023) suggest that the valence-based dissociation between personal and collective cognition may be tied to the fluency-based cueing techniques that have dominated early studies in this area. Moreover, Zerr et al (2023) and Habermas et al (2023) suggest that additional work with narrative-based techniques is needed to better understand not just what events come to mind but the situational context, meaning, and function of those events (see also Daley et al, 2023; Hirst & Topçu, 2023).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Another central aspect of our account of the valence-based differences that emerge between personal and national event cognition is rooted in the role of cultural scripts and narratives that guide both the lives of individuals and nations. Hirst and Topçu (2023) suggest that cultural scripts may be more suitable for explaining such effects at the personal level than the national level. Indeed, Janssen (2015) attempted to determine whether public events, which they also found to be construed by participants as more negative than positive, might be organized according to a cultural script but did not find any evidence that this was the case.…”
Section: Scripts Narratives and Temporal Trajectoriesmentioning
confidence: 99%
“…The present research showed that the relation between valence, perceived agency, and personal and collective mental time travel can be context specific. The valence-based dissociation found in Shirkanth et al (2018) is not always robust even in WEIRD countries (Hirst & Topçu, 2023). Certain public events that intersect personal and collective domains, like the COVID-19 pandemic, can alter the patterns of differences between personal and collective MTT, especially for future thought.…”
Section: Discussionmentioning
confidence: 95%
“…There are a few studies of personal and collective MTT that have failed to show the aforementioned dissociation between personal and collective MTT or demonstrate an attenuated dissociation (Hirst & Topçu, 2023). One such study involved a sample from a non-WEIRD country, China, in which Deng et al (2022) did not observe a dissociation in valence biases.…”
mentioning
confidence: 99%